2021
DOI: 10.3389/fnhum.2020.587594
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Integration Impairments in Primary Progressive Aphasia: Evidence From Eye-Tracking

Abstract: Primary progressive aphasia (PPA) is a degenerative disease affecting language while leaving other cognitive facilities relatively unscathed. The agrammatic subtype of PPA (PPA-G) is characterized by agrammatic language production with impaired comprehension of noncanonical filler-gap syntactic structures, such as object-relatives [e.g., The sandwich that the girl ate (gap) was tasty], in which the filler (the sandwich) is displaced from the object position within the relative clause to a position preceding bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Recent on-line sentence comprehension studies demonstrated abnormal thematic integration in nfvPPA, but not lvPPA using eye-tracking (Walenski, Mack, Mesulam, & Thompson, 2020), and abnormal ERP (reduced p600) to verb-argument structure violations in both subtypes, with nfvPPA also showing no evidence of morphosyntactic violation detection (Barbieri et al, 2021). Indeed, the strong association between sentence-processing impairments (as measured by sentence production on the NAT which included written labels for the agent, verb, and patient) and verb performance supported hypotheses of the neural separation of integration processes (e.g., thematic integration), engaging primarily left IFG/MFG and pSTS (in line with Bornkessel-Schlesewsky & Schlesewsky, 2013;Lukic et al, 2021;Shapiro, Moo, & Caramazza, 2006).…”
Section: Distinct Patterns Of Cortical Atrophy Associated With Noun A...mentioning
confidence: 97%
“…Recent on-line sentence comprehension studies demonstrated abnormal thematic integration in nfvPPA, but not lvPPA using eye-tracking (Walenski, Mack, Mesulam, & Thompson, 2020), and abnormal ERP (reduced p600) to verb-argument structure violations in both subtypes, with nfvPPA also showing no evidence of morphosyntactic violation detection (Barbieri et al, 2021). Indeed, the strong association between sentence-processing impairments (as measured by sentence production on the NAT which included written labels for the agent, verb, and patient) and verb performance supported hypotheses of the neural separation of integration processes (e.g., thematic integration), engaging primarily left IFG/MFG and pSTS (in line with Bornkessel-Schlesewsky & Schlesewsky, 2013;Lukic et al, 2021;Shapiro, Moo, & Caramazza, 2006).…”
Section: Distinct Patterns Of Cortical Atrophy Associated With Noun A...mentioning
confidence: 97%
“…These sample sizes were established in view of the protocols applied in many other studies Kalénine, Mirman, Middleton, et al, 2012;Lee et al, 2014 ;Merck et al, 2020;Mirman et al, 2011;Mirman & Graziano, 2012a;Walenski et al, 2020) using both equivalent paradigm and statistical approach (see below for description).…”
Section: Participantsmentioning
confidence: 99%
“…Combined with a statistical approach allowing changes in gaze behavior to be analyzed over time, it has been successfully used to compare the amplitude and time course of taxonomic and thematic processing Kalénine, Mirman, Middleton, et al, 2012;Merck et al, 2020;Mirman & Graziano, 2012a;Mirman & Graziano, 2012b;Mirman & Magnuson, 2009). As time courses of gaze data involve multiple data point, the method is powerful, and allows to demonstrated differences in taxonomic and thematic processing even in small samples of participants (from 6-8 for patient groups to 15-20 for healthy participants, see Mirman et al, 2011; for equivalent sample sizes see also Kalénine, Mirman, Middleton, et al, 2012;Lee et al, 2014 ;Merck et al, 2020;Mirman & Graziano, 2012a;Walenski et al, 2020). Moreover, it can highlight both reduced/delayed (reflecting impaired semantic activation) and increased/earlier (reflecting exaggerated semantic activation) semantic competition .…”
Section: Introductionmentioning
confidence: 99%